Integrative Analysis Identified IRF6 and NDST1 as Potential Causal Genes for Ischemic Stroke - Mo, Xing-Bo; Lei, Shu-Feng; Zhang, Yong-Hong; Zhang, Huan (Frontiers in Neurology, 2019)
Objective: To highlight potential functional variants and causal genes for ischemic stroke (IS) in genomic loci identified by genome-wide association studies (GWAS). Methods: We examined the association between m6A-SNPs and IS in large scale GWAS. Furthermore, eQTL analysis was performed to evaluate the effect of m6A-SNPs on gene expression. The top associations between m6A-SNPs and gene expressions were validated in 40 individuals from the Chinese Han population. Besides, we applied differential expression analysis and Mendelian randomization (MR) analysis to detect potential causal genes for IS. Results: We found 310 (7.39%) m6A-SNPs which were nominally associated with IS. The proportion of m6A-SNPs with P values < 0.05 for IS was significantly higher than the non-m6A-SNPs (95%CI: [5.84%, 7.36%], P = 0.02). We found that the IS-associated m6A-SNP rs2013162 was associated with IRF6 expression (P = 6.30 × 10-23), meanwhile IRF6 was differentially expressed between IS cases and controls (P = 6.15 × 10-3) and showed a causal association with IS (P = 3.64 × 10-4). Similar results were found for m6A-SNP rs2273235 in the NDST1 gene which was associated with cardioembolic stroke (P = 8.47 × 10-3). The associations of rs2013162 and rs2273235 with the expression of IRF6 and NDST1 were validated in blood cells (P = 0.0247 and 0.0007), respectively. Conclusions: This study showed that m6A-SNPs may affect IS risk through altering gene expressions. The results suggested that m6A might play a role in IS etiology and gene expressions that affected by m6A may be causal factors for IS.